Composition for chemically excited silicon-aluminum self-sensing material, self-sensing material and preparation method and application of self-sensing material
By adding carbon black and steel fibers to chemically excited silicon-aluminum materials, and preparing chemically excited silicon-aluminum self-perception materials with excellent mechanical properties and conductive properties, the shortcomings of traditional materials in terms of mechanical properties and conductivity are solved, and the comprehensive effects of high strength, high toughness, high conductivity and low cost are achieved.
Patent Information
- Application Number
- CN202510092116.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-21
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2045-01-21
AI Technical Summary
Chemically excited silicon-aluminum materials have problems with low flexural strength and poor toughness in terms of mechanical properties, and traditional self-perceived concrete has reduced conductivity, insufficient workability and high cost, which limits its long-term performance and large-scale application.
A composition for chemically excited silicon-aluminum self-sensing material is provided, which contains a main agent and an auxiliary agent. The main agent consists of a first component, aggregate, a second component and a chemical exciter. The second component is a combination of carbon black and steel fibers. The chemical exciter contains alkali metal oxides and prepares the material by mixing contact and curing treatment.
This material has excellent flexural strength and toughness, good conductivity, high sensitivity and low cost, and is suitable for intelligent health monitoring of bridges, large concrete beams and beam column nodes.
Smart Images

Figure BDA0005251865370000111 
Figure BDA0005251865370000121
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of chemically excited materials, and in particular to a composition for chemically excited silicon-aluminum self-sensing materials, a self-sensing material, and a preparation method and application thereof. Background Art
[0002] Buildings and infrastructure often suffer from aging and deterioration during their long-term service, facing potential risks to their structural safety and integrity, especially those high-value assets that are approaching the end of their design life.
[0003] For critical components in structures, accurate structural health monitoring is necessary to assess the potential defects and health status of the structure. The accuracy of assessment and prediction is crucial to determine whether infrastructure or structural components need to be modified or replaced.
[0004] Self-sensing concrete has the advantages of low cost, good durability and strong adaptability. It can monitor stress, strain, cracks, fatigue and other damage and deformation in the structure through changes in resistivity in concrete.
[0005] Traditional self-sensing concrete mostly uses silicate cement as a cementing material and carbon-based materials as conductive fillers. Chemically excited silica-alumina materials are a new type of green building structural material, mainly made of silicate minerals (such as metallurgical waste slag, coal-fired thermal power plant waste and municipal solid waste, etc.) as raw materials, and are prepared by chemical reaction with alkaline activators. This type of material is formed under normal temperature or high temperature curing conditions, and has a unique microporous structure and a high alkaline ion content, which gives it excellent ionic conductivity and multifunctional properties. In addition, chemically excited silica-alumina materials also have high early strength and significant corrosion resistance, making them ideal cementing materials for preparing self-sensing concrete. Despite this, chemically excited silica-alumina materials still have some shortcomings in mechanical properties, especially low flexural strength and poor toughness.
[0006] CN109081643A discloses a carbon fiber / alkali-activated composite pressure-sensitive material and a preparation method thereof. The composite pressure-sensitive material comprises the following components by weight: 0-80 parts of fly ash, 20-100 parts of slag, 0.23-1.13 parts of carbon fiber, 118-153 parts of sand, 45-55 parts of alkaline activator, 0.3-0.5 parts of dispersant and 0.1-0.2 parts of defoamer. However, this type of concrete often faces problems such as decreased conductivity, insufficient workability and excessive cost, which limits its long-term performance and large-scale application. At the same time, single carbon fiber materials often face problems such as low strength, low elastic modulus and high brittleness, and their application has an adverse effect on the safety of the structure and the sensitivity of perception. Summary of the invention
[0007] The purpose of the present invention is to provide a chemically excited silicon-aluminum self-sensing material with high strength, high toughness, high conductivity, high sensitivity and low cost.
[0008] In order to achieve the above-mentioned object, the first aspect of the present invention provides a chemically excited silicon-aluminum self-sensing material composition, the composition contains a main agent and an auxiliary agent; the main agent is a first component, an aggregate, a second component and a chemical activator;
[0009] Relative to 100 parts by weight of the first component, the content of the aggregate is 90-110 parts by weight, the content of the second component is 18-36 parts by weight, and the content of the chemical activator is 35-45 parts by weight;
[0010] Based on the total weight of the first component, the first component contains 45-60wt% of slag, 5-35wt% of metakaolin and 5-20wt% of silica fume;
[0011] The second component is carbon black and steel fiber in a mass ratio of 1:2.5-6.5; and the specific surface area of the carbon black is 50-70m 2 / g, conductivity is 10-15S / cm, average particle size is 40-50nm;
[0012] The modulus of the chemical activator is less than 0.8, and the content of alkali metal oxide in the chemical activator is 3-4wt%.
[0013] The second aspect of the present invention provides a method for preparing a chemically excited silicon-aluminum self-sensing material, which is carried out using the components in the chemically excited silicon-aluminum self-sensing material composition described in the first aspect, comprising:
[0014] (1) mixing and contacting the components in the main agent and the components in the auxiliary agent to obtain a slurry;
[0015] (2) The slurry is cured to obtain the chemically excited silicon-aluminum self-sensing material.
[0016] The third aspect of the present invention provides a chemically excited silicon-aluminum self-sensing material prepared by the method described in the second aspect.
[0017] The fourth aspect of the present invention provides the application of the chemically excited silicon-aluminum self-sensing material described in the third aspect in the field of building materials.
[0018] The chemically excited silicon-aluminum self-sensing material obtained by using the chemically excited silicon-aluminum self-sensing material composition provided by the present invention has excellent flexural strength and good toughness, and the raw materials in the self-sensing material are low-carbon, environmentally friendly and low-cost. It is suitable for intelligent health monitoring of key structures such as bridges, large concrete beams and beam-column joints under bending stress, and can also be applied to cast-in-place nodes of prefabricated buildings, thereby playing a role in real-time monitoring of key parts.
[0019] The method for preparing the chemically excited silicon-aluminum self-sensing material provided by the present invention is simple to operate and is conducive to large-scale production. DETAILED DESCRIPTION
[0020] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0021] As mentioned above, the first aspect of the present invention provides a composition for chemically excited silicon-aluminum self-sensing material, the composition contains a main agent and an auxiliary agent; the main agent is a first component, an aggregate, a second component and a chemical activator;
[0022] Relative to 100 parts by weight of the first component, the content of the aggregate is 90-110 parts by weight, the content of the second component is 18-36 parts by weight, and the content of the chemical activator is 35-45 parts by weight;
[0023] Based on the total weight of the first component, the first component contains 45-60wt% of slag, 5-35wt% of metakaolin and 5-20wt% of silica fume;
[0024] The second component is carbon black and steel fiber in a mass ratio of 1:2.5-6.5; and the specific surface area of the carbon black is 50-70m 2 / g, conductivity is 10-15S / cm, average particle size is 40-50nm;
[0025] The modulus of the chemical activator is less than 0.8, and the content of alkali metal oxide in the chemical activator is 3-4wt%.
[0026] The present invention provides examples illustratively to illustrate the meaning of the content of alkali metal oxides in the present invention. Exemplarily, when the chemical activator is a sodium-based activator (Na2O·nSiO2), the content of alkali metal oxides in the sodium-based activator is the ratio of the mass of Na2O to the total mass of Na2O and SiO2 in the chemical activator; when the chemical activator is a potassium-based activator (K2O·nSiO2), the content of alkali metal oxides in the potassium-based activator is the ratio of the mass of K2O to the total mass of K2O and SiO2 in the chemical activator.
[0027] Preferably, the chemical activator is a potassium-based activator.
[0028] According to a preferred embodiment, the potassium-based activator is prepared by a method comprising the following steps:
[0029] Potassium silicate, potassium hydroxide and water are mixed to obtain a potassium-based activator.
[0030] The present invention has no special requirements for the mixing method, and it is only necessary to make potassium silicate, potassium hydroxide and water uniformly mixed, and those skilled in the art can select according to needs. For example, the mixing is carried out at 20-25° C. and a rotation speed of 200-400 rpm for 10-20 minutes.
[0031] It should be noted that the present invention has no special requirements on the type of water, which can be deionized water or ultrapure water for example, and those skilled in the art can choose according to their needs. The present invention is only described once in one aspect without repeating the description, and those skilled in the art should not understand it as a limitation of the present invention.
[0032] Preferably, the mass ratio of the straight steel fiber to the end hook steel fiber in the steel fiber is 1:0.25-1. The inventors of the present invention have found that under this preferred condition, the obtained chemically excited silicon-aluminum self-sensing material has the best flexural strength and toughness enhancement effect.
[0033] Preferably, the steel fiber has a diameter of 0.18-0.23 mm and a length of 12-14 mm.
[0034] Preferably, the modulus of the chemical stimulant is 0.6-0.7. The inventors of the present invention have found that under this preferred condition, the obtained chemically stimulated silicon-aluminum self-sensing material has excellent construction performance and mechanical strength.
[0035] Preferably, based on the total weight of the first component, the first component contains 50-60 wt% of slag, 25-35 wt% of metakaolin and 5-15 wt% of silica fume.
[0036] Preferably, the average particle size of the silica fume is 5-9 μm, and the specific surface area is 1.75×10 5 -1.80×10 5 m 2 / g, silicon dioxide content ≮96wt%.
[0037] According to a preferred specific implementation, the content of silicon dioxide in the slag is 30-45wt%, the content of aluminum oxide is 10-20wt%, and the content of calcium oxide is 35-50wt%.
[0038] According to another preferred embodiment, the content of silicon dioxide in the metakaolin is 45-60wt%, the content of aluminum oxide is 35-50wt%, and the content of ferric oxide is less than 2wt%;
[0039] Preferably, the aggregate is quartz sand.
[0040] Preferably, the average particle size of the quartz sand is 0.1-1.0 mm.
[0041] It should be noted that the average particle size in the present invention refers to the particle size corresponding to when the cumulative particle size distribution fraction in the powder sample reaches 50% when tested by a laser particle size analyzer.
[0042] It should be noted that, in the present invention, the modulus of the chemical activator is the ratio of the molar amount of SiO2 to the molar amount of the alkali metal oxide in the chemical activator. Exemplarily, when the chemical activator is a potassium-based activator (K2O·nSiO2), the modulus of the chemical activator is the ratio of the molar amount of SiO2 to the molar amount of K2O.
[0043] Preferably, the auxiliary agent includes a dispersant and a defoamer;
[0044] Relative to 100 parts by weight of the first component, the content of the dispersant is 0.01-6 parts by weight, and the content of the defoaming agent is 0.005-3 parts by weight.
[0045] Preferably, the dispersant is selected from at least one of polyvinyl pyrrolidone, polyacrylic acid salt, polyacrylamide, polyvinylidene fluoride and sodium dodecylbenzene sulfonate.
[0046] Preferably, the defoaming agent is selected from at least one of tributyl phosphate, polydimethylsiloxane, polypropylene glycol and polyoxyethylene.
[0047] As mentioned above, the second aspect of the present invention provides a method for preparing a chemically excited silicon-aluminum self-sensing material, which is carried out using the components in the chemically excited silicon-aluminum self-sensing material composition described in the first aspect, and comprises:
[0048] (1) mixing and contacting the components in the main agent and the components in the auxiliary agent to obtain a slurry;
[0049] (2) The slurry is cured to obtain the chemically excited silicon-aluminum self-sensing material.
[0050] According to a preferred embodiment, in step (1), the step of mixing and contacting the components in the main agent and the components in the auxiliary agent comprises:
[0051] S1: first stirring and mixing the additive, the chemical stimulant and the carbon black in the second component to obtain a mixed slurry I;
[0052] S2: performing a second stirring mixing on the mixed slurry I and the mixed material I containing the first component to obtain a mixed slurry II;
[0053] S3: The steel fibers in the second component and the mixed material II containing the mixed slurry II and aggregate are subjected to a third stirring and mixing process to obtain the slurry.
[0054] Preferably, in step S1, the first stirring and mixing conditions include: a rotation speed of 500-1000 rpm and a time of 20-60 min.
[0055] Preferably, in step S2, the second stirring and mixing conditions include: first stirring at 120-140 rpm for 0.5-1 min, and then stirring at 260-300 rpm for 0.5-1.5 min.
[0056] Preferably, in step S3, the conditions for the third stirring and mixing include: a rotation speed of 260-300 rpm and a time of 0.5-1.5 min.
[0057] According to a preferred embodiment, in step S3, the mixed material II is prepared by a method comprising the following steps:
[0058] The mixed slurry II and the aggregate are first stirred at 120-140 rpm for 0.5-1 min, and then stirred at 260-300 rpm for 0.5-1.5 min to obtain the mixed material II.
[0059] Preferably, in step (2), the curing treatment conditions include: temperature of 15-25° C. and humidity of 60-90%.
[0060] According to a preferred specific implementation, in step (2), before the curing treatment, the slurry is first cast into shape and covered with plastic wrap, and then left to stand for 18-30 hours in an environment of 18-22°C and relative humidity ≥90% before the curing treatment is performed.
[0061] Preferably, the curing treatment is carried out in a constant temperature and humidity curing box.
[0062] As mentioned above, the third aspect of the present invention provides a chemically excited silicon-aluminum self-sensing material prepared by the method described in the second aspect.
[0063] As mentioned above, the fourth aspect of the present invention provides the application of the chemically excited silicon-aluminum self-sensing material described in the third aspect in the field of building materials.
[0064] The present invention will be described in detail below by way of examples. In the following examples, unless otherwise specified, the raw materials are all commercially available or homemade.
[0065] Potassium silicate: purchased from Shanghai MacLean Biochemical Technology Co., Ltd., brand number P850160.
[0066] Slag: The content of silicon dioxide is 32.09wt%, the content of aluminum oxide is 16.55wt%, and the content of calcium oxide is 37.65wt%, which is purchased from Jiyuan Guotai Micro Powder Technology Co., Ltd.
[0067] Metakaolin: the content of silicon dioxide is 47.19wt%, the content of aluminum oxide is 49.11wt%, and the content of iron oxide is 0.79wt%, which is purchased from Inner Mongolia Chaoneng New Materials Co., Ltd.
[0068] Silica fume: SiO2 content is 97.42wt%, average particle size is 7.73μm, specific surface area is 1.80×10 5 m 2 / g, purchased from Shanghai Tiankai Building Materials Technology Co., Ltd., brand 970 silicon powder.
[0069] Aggregate: quartz sand, with an average particle size of 0.4 mm. Quartz sands of grades 5, 6 and 7 purchased from Anhui Jingyou Sand and Gravel Sales Co., Ltd. are mixed in a mass ratio of 1:1:1 and used.
[0070] Carbon Black:
[0071] Carbon black I: Specific surface area is 62m 2 / g, conductivity is 12S / cm, average particle size is 45nm, purchased from Dongguan Kelude Innovation Technology Co., Ltd., brand name Super P Li.
[0072] Carbon black DI: specific surface area is 420m 2 / g, resistivity is about 0.67S / cm, average particle size is 23-28nm, purchased from Suqian Nakaite New Material Technology Co., Ltd., brand Super-P.
[0073] Steel Fiber:
[0074] Steel fiber I: The mass ratio of the straight steel fiber to the end hook steel fiber is 1:1, the diameter of the steel fiber is 0.2 mm, and the length is 13 mm; the straight steel fiber is purchased from Shanghai Shenxiang Concrete Fiber Co., Ltd. with the brand name SAP0213SW, and the end hook steel fiber is purchased from Shanghai Shenxiang Concrete Fiber Co., Ltd. with the brand name SAP0213SWH.
[0075] Steel fiber II: a straight steel fiber with a diameter of 0.2 mm and a length of 13 mm, purchased from Shanghai Shenxiang Concrete Fiber Co., Ltd. with a brand name of SAP0213SW.
[0076] Additives:
[0077] Dispersant: Polyvinyl pyrrolidone, purchased from Shanghai MacLean Biochemical Technology Co., Ltd., brand number P816205.
[0078] Defoaming agent: tributyl phosphate, purchased from Shanghai MacLean Biochemical Technology Co., Ltd., brand number T818517.
[0079] The following preparation examples and comparative preparation examples are used to illustrate the preparation of potassium-based activators.
[0080] Preparation Example 1
[0081] Potassium silicate, potassium hydroxide and water were mixed (mixed at 25°C and 300 rpm for 15 min) to obtain a potassium-based activator, named chemical activator I;
[0082] The specific formula is shown in Table 1.
[0083] Unless otherwise specified, Preparation Example 2 was carried out using a method similar to Preparation Example 1, except that the raw material formula was specifically shown in Table 1.
[0084] Comparative Preparation Example 1
[0085] This preparation example is carried out by a method similar to that of Preparation Example 1, except that the formula is different from that in Preparation Example 1; a potassium-based activator is prepared and named as chemical activator DI. The specific formula is shown in Table 1.
[0086] Table 1
[0087] Preparation Example 1 Preparation Example 2 Comparative Preparation Example 1 Potassium silicate / g 3.39 2.82 4.52 Potassium hydroxide / g 5.85 6.07 5.42 Deionized water / g 35.71 36.76 33.61 Modulus of potassium-based activators 0.6 0.5 0.8 Content of alkali metal oxide in potassium-based activator / wt% 3.39 3.39 3.39 Nomenclature of potassium-based activators Chemical activator I Chemical Activator II Chemical activator DI
[0088] Example 1
[0089] This example is used to illustrate the preparation of chemically excited silicon-aluminum self-sensing material according to the formula and process parameters shown in Table 2 and the following steps:
[0090] (1) first stirring and mixing the auxiliary agent, the chemical stimulant and the carbon black in the second component to obtain a mixed slurry I;
[0091] (2) subjecting the mixed slurry I and the mixed material I containing the first component to a second stirring mixing to obtain a mixed slurry II;
[0092] (3) stirring the mixed slurry II and the aggregate at 140 rpm for 1 min and then stirring at 285 rpm for 1 min to obtain the mixed material II; performing a third stirring mixing on the steel fiber in the second component and the mixed material II containing the mixed slurry II and the aggregate to obtain the slurry;
[0093] (4) curing the slurry to obtain the chemically excited silicon-aluminum self-sensing material;
[0094] The first stirring and mixing was performed at a speed of 800 rpm for 40 min;
[0095] Second stirring and mixing: first stirring at 140 rpm for 1 min, then stirring at 285 rpm for 1 min;
[0096] The third stirring and mixing was performed at a speed of 285 rpm for 1 min;
[0097] The temperature of the curing treatment was 20°C and the humidity was 90%.
[0098] Unless otherwise specified, Example 2 is carried out in a similar manner to Example 1, except for the raw material formula, as shown in Table 2, to prepare the chemically excited silicon-aluminum self-sensing material.
[0099] Example 3
[0100] This embodiment is carried out in a similar manner to that of Embodiment 1, except that an equal amount of steel fiber II is used in this embodiment to replace the steel fiber I in Embodiment 1, and the unlisted parts are the same as those in Embodiment 1, to prepare the chemically excited silicon-aluminum self-sensing material.
[0101] Example 4
[0102] This embodiment is carried out in a similar manner to that of Embodiment 1, except that an equal weight of chemical stimulant II is used in this embodiment to replace the chemical stimulant I in Embodiment 1, and the unlisted parts are the same as those in Embodiment 1, to prepare the chemically excited silicon-aluminum self-sensing material.
[0103] Comparative Example 1
[0104] This comparative example is carried out in a similar manner to Example 1, except that an equal amount of carbon black DI is used to replace the carbon black I in Example 1, and the unlisted parts are the same as in Example 1, to prepare the chemically excited silicon-aluminum self-sensing material.
[0105] Comparative Example 2
[0106] This comparative example is carried out in a similar manner to Example 1, except that: on the basis of keeping the amount of the second component unchanged, the mass ratio of the carbon black and steel fiber in the second component is adjusted to 1:0.65, and the unlisted parts are the same as Example 1, to prepare the chemically excited silicon-aluminum self-sensing material.
[0107] Comparative Example 3
[0108] This comparative example is carried out in a similar manner to Example 1, except that an equal amount of chemical stimulant DI is used to replace the chemical stimulant I in Example 1, and the unlisted parts are the same as in Example 1, to prepare the chemically excited silicon-aluminum self-sensing material.
[0109] Table 2
[0110]
[0111] Test Case
[0112] (1) The flexural strength of the chemically excited silicon-aluminum self-sensing material prepared in the above example was tested by the method specified in GB / T 17671-2021 (flexural strength after 28 days of curing);
[0113] (2) The bending toughness coefficient of the chemically excited silicon-aluminum self-sensing material prepared in the above example was tested using the method specified in JSCE SF-4. Toughness T b represents the area under the load-displacement curve when the deflection is δ; L represents the span of the specimen; b represents the width of the specimen; h represents the height of the specimen).
[0114] (3) The compressive strength of the chemically excited silicon-aluminum self-sensing material prepared in the above example was tested by the method specified in GB / T 17671-2021 (compressive strength after 28 days of curing);
[0115] (4) The resistance of the chemically excited silicon-aluminum self-sensing material prepared in the above example was tested by the method specified in https: / / doi.org / 10.1016 / j.jobe.2022.105022 (resistance after 28 days of curing treatment);
[0116] (5) The bending strain sensitivity GF of the chemically excited silicon-aluminum self-sensing material prepared in the above example was tested by the method specified in https: / / doi.org / 10.1021 / acsami.7b00419 (strain sensitivity after 28 days of curing treatment, GF = |FCR| / ε, FCR is the resistivity change rate, ε is the strain under bending stress);
[0117] The results of the above performance tests are shown in Table 3.
[0118] Table 3
[0119]
[0120] It can be seen from the above results that the chemically excited silicon-aluminum self-sensing material prepared by the chemically excited silicon-aluminum self-sensing material composition provided by the present invention has good flexural strength and compressive strength, good electrical conductivity and high bending strain sensitivity, and is particularly suitable for intelligent health monitoring of key structures such as bridges, large concrete beams and beam-column joints under bending stress.
[0121] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A chemically excited silicon-aluminum self-sensing material composition, characterized in that: The composition contains a main agent and an auxiliary agent; the main agent is a first component, aggregate, a second component and a chemical activator; Relative to 100 parts by weight of the first component, the content of the aggregate is 90-110 parts by weight, the content of the second component is 18-36 parts by weight, and the content of the chemical activator is 35-45 parts by weight; Based on the total weight of the first component, the first component contains 45-60wt% of slag, 5-35wt% of metakaolin and 5-20wt% of silica fume; The second component is carbon black and steel fiber in a mass ratio of 1:2.5-6.5; and the specific surface area of the carbon black is 50-70m 2 / g, conductivity is 10-15S / cm, average particle size is 40-50nm; The modulus of the chemical activator is less than 0.8, and the content of alkali metal oxide in the chemical activator is 3-4wt%.
2. The composition according to claim 1, characterized in that The mass ratio of the straight steel fiber to the end hook steel fiber in the steel fiber is 1:0.25-1.
3. The composition according to claim 1 or 2, characterized in that The steel fiber has a diameter of 0.18-0.23 mm and a length of 12-14 mm; And / or, the modulus of the chemical stimulant is 0.6-0.
7.
4. The composition according to any one of claims 1 to 3, characterized in that Based on the total weight of the first component, the first component contains 50-60wt% of slag, 25-35wt% of metakaolin and 5-15wt% of silica fume; And / or, the average particle size of the silica fume is 5-9 μm, and the specific surface area is 1.75×10 5 -1.80×10 5 m 2 / g, silicon dioxide content ≮96wt%.
5. The composition according to any one of claims 1 to 4, characterized in that The slag contains 30-45 wt% silicon dioxide, 10-20 wt% aluminum oxide and 35-50 wt% calcium oxide; And / or, the content of silicon dioxide in the metakaolin is 45-60wt%, the content of aluminum oxide is 35-50wt%, and the content of ferric oxide is less than 2wt%; And / or, the aggregate is quartz sand.
6. The composition according to any one of claims 1 to 5, characterized in that The auxiliary agents include dispersants and defoamers; Relative to 100 parts by weight of the first component, the content of the dispersant is 0.01-6 parts by weight, and the content of the defoaming agent is 0.005-3 parts by weight.
7. A method for preparing a chemically excited silicon-aluminum self-sensing material, characterized in that: The method is carried out using the components in the chemically excited silicon-aluminum self-sensing material composition according to any one of claims 1 to 6, and comprises: (1) mixing and contacting the components in the main agent and the components in the auxiliary agent to obtain a slurry; (2) The slurry is cured to obtain the chemically excited silicon-aluminum self-sensing material.
8. The method according to claim 7, characterized in that In step (1), the step of mixing and contacting the components in the main agent and the components in the auxiliary agent comprises: S1: first stirring and mixing the additive, the chemical stimulant and the carbon black in the second component to obtain a mixed slurry I; S2: performing a second stirring mixing on the mixed slurry I and the mixed material I containing the first component to obtain a mixed slurry II; S3: The steel fibers in the second component and the mixed material II containing the mixed slurry II and aggregate are subjected to a third stirring and mixing process to obtain the slurry.
9. The chemically excited silicon-aluminum self-sensing material prepared by the method according to claim 7 or 8.
10. Use of the chemically excited silicon-aluminum self-sensing material according to claim 9 in the field of building materials.
Citation Information
Patent Citations
Geopolymer composition, geopolymer material and preparation method of geopolymer material
CN104098281A
Preparation method of alkali-activated high-silica bauxite ore based gel material with adjustable electric conductivity
CN105731895A
Graphene oxide-nano mineral enhanced geopolymer material and preparation method thereof
CN110981298A
Conductive heating high-strength cement-based composite fiber material and preparation method thereof
CN111393098A
Preparation method of high-heating electric shock curing concrete structure
CN114394851A